Novel r(2)(p25q31) Cytogenetic Abnormality in a Pediatric Patient with Acute Leukemia of Ambiguous Lineage. (January 2015) - Kim, Jaehyup; Bu, Lihong; Koduru, Prasad R.; Wilson, Kathleen S.; Fuda, Franklin S.; Kumar, Kirthi R.; Timmons, Charles F.; Slone, Tamra L.; Luu, Hung S.
We describe a case of acute leukemia of ambiguous lineage with a novel cytogenetic abnormality. A 1-year-old boy presented with abnormal complete blood count findings, and was found to have blasts and mild dysgranulopoiesis. The blasts showed immunophenotypic evidence of myeloid and T-lineage differentiation. Subsequent cytogenetic analysis showed r(2)(p25q31) as the sole stem line cytogenetic defect with clonal evolution. While cytogenetic abnormalities can have a critical role in the classification and prognostication of acute lymphoblastic and acute myeloid leukemia, the significance of cytogenetic abnormalities in acute leukemia of ambiguous lineage remains unclear. This finding has not been reported previously to the best of our knowledge.